2018
DOI: 10.1101/425942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xrs2 and Tel1 independently contribute to MR-mediated DNA tethering and replisome stability

Abstract: The yeast Mre11-Rad50-Xrs2 (MRX) complex has structural, signaling and catalytic functions in the cellular response to DNA damage. Xrs2, the eukaryotic-specific component of the complex, is required for nuclear import of Mre11 and Rad50, and to recruit the Tel1 kinase to damage sites. We show that nuclear-localized MR complex (Mre11-NLS) catalyzes homology-dependent repair without Xrs2, but MR cannot activate Tel1 and it fails to tether DSBs resulting in sensitivity to genotoxins, replisome instability and inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
(111 reference statements)
2
2
0
Order By: Relevance
“…We note that expression of MRE11 ‐NLS in xrs2 Δ mutant strain restores ends resection and DSB repair by SDSA but not ends tethering. This result provides further support for the role of resection rather than end tethering in proper DSB repair (Oh et al, 2018).…”
Section: Resultssupporting
confidence: 63%
“…We note that expression of MRE11 ‐NLS in xrs2 Δ mutant strain restores ends resection and DSB repair by SDSA but not ends tethering. This result provides further support for the role of resection rather than end tethering in proper DSB repair (Oh et al, 2018).…”
Section: Resultssupporting
confidence: 63%
“…However, in the context of tel1-kd, the CPT sensitivity of each of the three was mitigated in comparison to the tel1∆ background. This suggests that the inactive Tel1 protein binds to, and enhances the functionality of the Mre11 complex via physical interaction as proposed previously [10,32,42]. Consistent with this idea, the effect of tel1-kd on CPT sensitivity was most pronounced in the Rad50-L1240F, mutant, which binds DNA in vitro at least 10 fold less well than Rad50-D67N or -D67Y ( Fig 5B).…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies suggest that Tel1 has a structural role in stabilizing Mre11 complex DSB association that is independent of its kinase activity [10,31,32]. We found that the effects of tel1-kd versus tel1∆ on the survival of SOF mutants exposed to CPT were different, and did not strictly correlate with the ability of the mutant gene products to recruit Tel1 to DSBs.…”
Section: Molecular Phenotypes Of Rad50 Sof Mutationsmentioning
confidence: 55%
See 1 more Smart Citation